Synchronizing Live Video Streaming Players Via Consensus - Gioacchino Manfredi; Luca De Cicco; Saverio Mascolo (European Control Conference (ECC), 2021)
Video streaming is the primary source of the global Internet traffic. Social media applications allow users to experience live streaming events together, even though not being in the same physical place. The current online video delivery architecture cannot ensure a synchronized video playback among geographically distributed users. Unsynchronized playback can become evident and negatively impact the users’ feelings of togetherness. In this paper, we show that the well- known consensus problem of simple integrators with saturated inputs is an appropriate mathematical framework to design a distributed playback synchronization mechanism. Furthermore, we propose a leader-following approach to ensure synchronization among users. Simulations on different network topologies confirm that the proposed approach is effective at enforcing asymptotic synchronization without having detrimental effects on the users’ perceived quality.